2014
DOI: 10.3892/mmr.2014.2075
|View full text |Cite
|
Sign up to set email alerts
|

Opposite effects of the gap junction blocker octanol on focal cerebral ischemia occluded for different durations

Abstract: Protectants and executioners have been demonstrated to be used by gap junctions in focal cerebral ischemia. Certain researchers hypothesized that the opposite role of gap junctions may be associated with the injury extent, which has been demonstrated to be highly correlated with occlusion duration. In order to examine this hypothesis directly, the effects of octanol, a frequently used drug, were examined to investigate the role of gap junctions, in rats following middle cerebral artery occlusion (MCAO) for 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Gap26 treatment led to a reduction in both Cx43 expression and activity, therefore reducing the infarct volume and improving the neurological function (9). Gap junction blocker carbenoxolone or octanol played protective roles in ischemic preconditioning or cerebral ischemia (16,17). Recent studies showed that inhibition of Cx43 hemichannels alleviated cerebral ischemia via the toll-like receptor (TLR4) or JAK2/STAT3 pathway (18,19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gap26 treatment led to a reduction in both Cx43 expression and activity, therefore reducing the infarct volume and improving the neurological function (9). Gap junction blocker carbenoxolone or octanol played protective roles in ischemic preconditioning or cerebral ischemia (16,17). Recent studies showed that inhibition of Cx43 hemichannels alleviated cerebral ischemia via the toll-like receptor (TLR4) or JAK2/STAT3 pathway (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that inhibition of Cx43 hemichannels alleviated cerebral ischemia via the toll-like receptor (TLR4) or JAK2/STAT3 pathway (18,19). Notably, the intervention of Cx43 or the gap junction occurred immediately after ischemia (during acute phase) in numerous experiments (9,(16)(17)(18)(19). In contrast, few studies investigated their roles in the subacute phase after focal ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…The total volume was calculated as the following equation: the total volume (%) = S · L , where S is the total infarct area and L is the thickness of slice. Then the infarct volume was assessed as a percentage of the ipsilateral hemispheric volume (%) as described previously (Ding et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…All the experimental procedures were carried out strictly in compliance with the NIH guidelines for the Care and Use of Laboratory Animals. Focal ischemia was induced by middle cerebral artery occlusion (MCAO) as previously reported (18). Briefly, rats were anesthetized with 350 mg/kg chloral hydrate via intraperitoneal injection.…”
Section: Methodsmentioning
confidence: 99%
“…Images were captured using an Olympus microscope (Olympus, Tokyo, Japan). To quantify GLT-1, GS and GFAP immunoreactivity (IR), measurement was performed with a computerized image analysis system (Image-Pro-Plus; Media Cybernetics, Silver Spring, MD, USA) according to a previously described method (18). Briefly, a density threshold was first set above the background level to identify the positively stained structure and the area occupied by these structures was measured as the positive area.…”
Section: Methodsmentioning
confidence: 99%